Community‐level responses of African carnivores to prescribed burning. Issue 1 (17th October 2021) - Gigliotti, Laura C.; Curveira‐Santos, Gonçalo; Slotow, Rob; Sholto‐Douglas, Craig; Swanepoel, Lourens H.; Jachowski, David S.
Abstract: Fires are common in many ecosystems world‐wide, and are frequently used as a management tool. Although the responses of herbivores to fire have been well‐studied, the responses of carnivores to fire remain unclear. In particular, post‐fire habitat changes, and the associated changes in prey availability, might affect the coexistence or competition of carnivore species within the larger carnivore community, but few studies have focused on how fires influence multiple carnivore species simultaneously. Using South African carnivores as our focal community, we explored relative changes in carnivore intensity of use in post‐fire landscapes associated with hypothesized changes in prey availability and top‐down suppression. We monitored carnivore intensity of use in relation to prescribed burning using camera traps, with a Before‐After‐Control‐Impact study design. We analysed the camera trap data using community N‐mixture models to understand how individual species, as well as the carnivore guild as a whole, respond to burning. Changes in carnivore intensity of use in response to prescribed burns were not uniform; however, no species decreased the intensity of use of post‐fire landscapes. The apex predator, the lion Panthera leo, increased the use of prey‐rich burnt areas, but other large carnivore species exhibited neutral responses to fire despite the associated prey increase. Responses of medium‐ and small‐sized carnivores were species specific, and included both neutral and positive responses. Positive responses to fire by lions and herbivores were short‐lived, and did not persist a year after burning occurred. Synthesis and applications . Our results indicate that fire does not promote carnivore coexistence by creating conditions for all carnivores to increase the use of burned areas, but that it also likely does not result in spatial avoidance of subordinate predators. Instead, fires might cause a suppression of opportunities for subordinate large carnivores because they need to avoid the apex predator, rather than take advantage of short‐term increased hunting opportunities in recently burned areas. Our results highlight the complexity of understanding species‐specific and community‐level responses of carnivores to fire, and overlooked the ecological effects of its use as a management tool. Abstract : Our results indicate that fire does not promote carnivore coexistence by creating conditions for all carnivores to increase the use of burned areas, but that it also likely does not result in spatial avoidance of subordinate predators. Instead, fires might cause a suppression of opportunities for subordinate large carnivores because they need to avoid the apex predator, rather than take advantage of short‐term increased hunting opportunities in recently burned areas. Our results highlight the complexity of understanding species‐specific and community‐level responses of carnivores to fire, and overlooked the ecological effects of its use as a management tool.